Compatibility of High-Density Polyethylene Grades with Biofuels - Weltschev, Margit; Werner, Jan; Haufe, Manuela; Heyer, Martina (Packaging technology & science, 2014)
The aim of this work was to study the interaction between high‐density polyethylene (HDPE) grades as material for dangerous goods packagings and biofuels such as E85 and biodiesel. Jerricans made of two polyethylene (PE) grades were filled with these fuels and exposed to temperatures of 20°C and 40°C for 1 year. Tensile properties (tensile strength, breaking elongation and elasticity modulus) and melt flow rate (MFR) were determined once a month, and Fourier transform infrared (FTIR) spectroscopy was used to evaluate changes in the chemical structure. Measurements of the MFR and tensile properties of the PE grades after 1 year of exposure to E85 showed only a slightly damaging influence. An increase in the peak of 1585 cm‐1 (C=C) stretching vibrations is visible in the FTIR spectra after the immersion tests with E85. Therefore, packagings made of HDPE grades are suitable for the transport of E85. An increase in the MFR with immersion time of the grades in biodiesel was measured, in particular, after 1 year of exposure. The elasticity modulus of the PE grades was reduced with immersion time. The FTIR spectra showed a broadening of the CO peak of 1740 cm‐1 and the appearance of the hydroxyl group at 3500 cm‐1. Both results are explained by secondary degradation products of the PE decomposition process caused by increasing unsaturated fatty acid content in the biodiesel. In light of the above mentioned, it was concluded that HDPE grades are not suitable as packaging materials for the transport of biodiesel. Copyright © 2013 John Wiley & Sons, Ltd. Biofuels including ethanol and biodiesel represent an important renewable fuel alternative to petroleum‐derived transport fuels. Measurements of the Melt Flow Rate and tensile properties of the polyethylene grades as well as the use of FTIR spectroscopy showed that packagings made of polyethylene grades are suitable for the transport of E85 but not for the transport of biodiesel which is subject to an ageing process by the formation of unsaturated fatty acids which accelerate the oxidative degradation of polyethylene.